Profil Keterampilan Kolaborasi Siswa SMP dalam Implementasi Model Pembelajaran Kooperatif Tipe STAD - Salma Indah Khoirunnisa; Elok Sudibyo (Program Studi Pendidikan IPA FKIP Universitas Jember, 2023)
The purpose of this study was to describe the collaboration skills of junior high school students in science learning on the implementation of the STAD type cooperative model in science learning. The research method used is descriptive quantitative with pre-experimental design. The subjects used in this study were class VIII E of SMP Negeri 1 Mojowarno. The data collection method used is observation during the learning process using observation sheets of student collaboration skills. The results of this study were that the average acquisition of students' collaboration skills at the first meeting was 64 with the collaborative category and at the second meeting was 79 with the collaborative category. The results of these percentages indicate that the collaboration skills of class VIII E students of SMP Negeri 1 Mojowarno can increase in the implementation of the STAD type cooperative learning model in science learning.